High expression of BBOX1 in paracancerous tissue is associated with poor prognosis in hepatocellular carcinoma patients - Runqi Fang; Yuling Zhan; Xiang Dong; Suwan Li; Minghui Yang; Yunxia Zhao; Yu Gao (Scientific Reports)
Abstract The molecular profile of paracancerous tissue has been reported to be prognostic for recurrence in patients with different cancers. This study investigated the clinical significance of the protein expression of gamma-butyrobetaine hydroxylase 1 (BBOX1) in tumor and paracancerous tissues of hepatocellular carcinoma (HCC) patients. This study assessed the role of BBOX1 mRNA in tumor and paracancerous tissues in HCC via bioinformatics analysis. The protein levels of BBOX1 in paired tumor and paracancerous tissues from 83 HCC patients were determined by immunohistochemistry. The associations among BBOX1 protein levels, clinicopathological characteristics and the survival probability of HCC patients were also analyzed. The results revealed that BBOX1 mRNA expression was significantly lower in HCC tissues than in noncancerous tissues. HCC patients with low BBOX1 mRNA expression had a significantly poorer overall survival than those with high BBOX1 expression did. Immunohistochemical analysis of BBOX1 protein expression further confirmed that its levels were markedly lower in HCC tissues than in paracancerous tissues. High BBOX1 expression in paracancerous tissues correlated with poor overall survival and disease-free survival in HCC patients. These findings suggest that the paracancerous BBOX1 expression might be a credible indicator for overall survival or disease-free survival in HCC patients.